(untitled) (UNIZIK Journal of Marketing, 2025)
As computerized commerce proceeds to advance, businesses are compelled to grasp and use these stages to remain competitive in a progressively online-centric commercial center. This study sought to look at user experience and e-loyalty in the e-commerce industry especially as it pertains to jumia company in Lagos State, Nigeria. the research survey method was adopted in this study. The population of the state was infinite hence a sample of 139 respondents was determined using Cochran formula for sample size determination. While the Convenience sample technique was used for this study. Primary Data was collected and analyzed using valid and reliable questionnaire with the Statistical Package for the Social Sciences (SPSS), version 25. The findings of the study indicated structure and navigation has positive significant impact on E-loyalty (p = 0.000 < 0.05, β = 0.978), speed and performance has positive significant impact on e-loyalty (p = 0.000 < 0.05, β = 0.992), The study concluded that ease of use significantly impacts e-loyalty p = 0.000 < 0.05, β = 0.994). The study recommended that management of Jumia should prioritize creating a well-organized structure with intuitive navigation, invest in a robust technology infrastructure to ensure fast load times and high performance, and focus on simplifying the user interface (UI) and making processes easier.